Pengaruh Pendapatan Asli Daerah (PAD), Dana Alokasi Umum (DAU), Belanja Modal dan Investasi Terhadap Pertumbuhan Ekonomi di Provinsi Jawa Timur Tahun 2020-2025 - Fitri Ramadhani; Agus Arifin (Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2026)
This study analyzes the impact of Regional Original Revenue (PAD), General Allocation Fund (DAU), Capital Expenditure, and Investment on economic growth in East Java during 2020–2024. Using panel data regression with the Fixed Effect Model (FEM), the results show that all variables have positive and significant effects, both partially and simultaneously. PAD strengthens fiscal capacity, DAU maintains stability in low-PAD regions, capital expenditure supports infrastructure and productivity, and investment increases production and employment. These findings align with Keynesian theory. The study highlights the need to optimize PAD, improve DAU allocation, enhance capital expenditure quality, and create a supportive investment climate.